Extrinsic rewards for employee creativity? The role of perceived organisational support, work engagement andintrinsic motivation - Aldabbas, Hazem (2023)
Purpose– This study aims to investigate the relationship between extrinsic rewards and employee creativity through the intervening mechanism of perceived organisational support (POS) and work engagement. The moderating role of intrinsic motivation on the relationship between work engagement and employee creativity is also examined. Design/methodology/approach– The authors report the results of a survey completed by 372 respondents employed in the United Arab Emirates. Structural equation modelling was applied to test the hypothesised relationships. Findings– The main findings are that extrinsic rewards influence employee creativity through POS and work engagement. Moreover, the effect of work engagement on employee creativity is moderated by intrinsic motivation. This modeleffect is stronger for employees with high intrinsic motivation. Research limitations/implications– Conveniencesamplingwasused,whichlimitsitsgeneralisability. Also, the data werecollected through a cross-sectional survey at one point in time.